A Clinical Picture of the Visual Outcome in Adamantiades-Behçet's Disease. (19th October 2015) - Figus, Michele; Posarelli, Chiara; Albert, Timothy G.; Talarico, Rosaria; Nardi, Marco
Abstract : Adamantiades-Behçet's disease is a multisystemic vasculitis with multiorgan involvement. Ocular disorders occur often in this syndrome typically in the form of a relapsing-remitting panuveitis and vasculitis and can lead to blindness as one of its most disabling complications if left untreated. There are known risk factors related with the worst visual prognosis, which require early and intensive treatment in order to obtain a rapid suppression of inflammation and to prevent future relapses. The management strategy to avoid vision loss and blindness currently involves the use of local and systemic drugs including steroids and immunosuppressive and biologic agents. This review aims to demonstrate how the introduction and the use of biologic agents improves the visual outcome of patients with Adamantiades-Behçet's disease.